Chinese- Australian Free Trade Agreement and How to Expedite the Current Negotiations (2013)
Tables and Figures. Introduction. The Importance of Trade between China and Australia. China and Australia: Their Comparative Advantage. Negotiating with China. Conclusions. Recommendations. Bibliography. Tables and Figures.